2018
DOI: 10.1111/jfbc.12566
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitrogen fertilizer micro-dosing on phenolic content, antioxidant, and anticholinesterase properties of aqueous extracts of three tropical leafy vegetables

Abstract: This work investigated the effect of fertilizer micro-dosing on in vitro antioxidant and antiacetylcholinesterase (AChE) properties of aqueous extracts of leaves of three vegetables (Solanum macrocarpon L., Amaranthus viridis L., and Telfairia occidentalis f. Hooke). Urea was combined (0, 20, 40, and 60 kg/ha) with cow manure (5 t/ha) or without cow manure (80 kg/ha) to grow the leafy vegetables. Significantly higher (p < .05) polyphenol extract yield was obtained with 60 kg N/ha when compared with other ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 51 publications
9
23
0
2
Order By: Relevance
“…Thus, nitrogen micro-dosing associated with organic fertilizer for growth of leafy vegetables that will be harvested at early maturity stage could be considered as beneficial to synthesis and activity of water-soluble free radical-scavenging polyphenols. Significant decreases in DPPH-RSA and FRAP with increase of nitrogen application doses as well as increase in these antioxidant activities with co-application of mineral and organic fertilizers had also been previously reported (Olarewaju et al, 2018;Sossa-Vihotogbé et al, 2013b;Stefanelli et al, 2011). High level of antioxidant activities found at the first two harvests could be linked to fertilization (for the first harvest) and to injury stress caused by first leaf harvest (for the second harvest).…”
Section: Variability In Antioxidant Activities As Response Of Fertilisupporting
confidence: 61%
See 2 more Smart Citations
“…Thus, nitrogen micro-dosing associated with organic fertilizer for growth of leafy vegetables that will be harvested at early maturity stage could be considered as beneficial to synthesis and activity of water-soluble free radical-scavenging polyphenols. Significant decreases in DPPH-RSA and FRAP with increase of nitrogen application doses as well as increase in these antioxidant activities with co-application of mineral and organic fertilizers had also been previously reported (Olarewaju et al, 2018;Sossa-Vihotogbé et al, 2013b;Stefanelli et al, 2011). High level of antioxidant activities found at the first two harvests could be linked to fertilization (for the first harvest) and to injury stress caused by first leaf harvest (for the second harvest).…”
Section: Variability In Antioxidant Activities As Response Of Fertilisupporting
confidence: 61%
“…Polyphenolic compounds were identified and quantified according to Olarewaju et al (2018) method with slight modifications. This method used a reversed-phase high-performance liquid chromatography system and was performed with a Varian 900-LC series system (Agilent Technologies, Santa Clara, California, USA) fitted with a C18 analytical column (250 × 4.6 mm, 5 µm) (Phenomenex Inc., Torrance, California, USA) pre-heated to 30 °C.…”
Section: Profile Of Main Polyphenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also reported that M. olefeira treated with NPK and compost (50 + 50%) in combination, depicted higher phenolics and flavonoids contents as compared to the control (Sarwar et al, 2019). According to Olarewaju et al (2018), the increased biomass in treated group can leads to reduced synthesis of secondary metabolites (polyphenolic compounds). The phenolic compounds contents are reduced when the phenylalanine amount is low as the protein accumulation increased when the nitrogen concentration is higher (Jones & Hartley, 1999).…”
Section: Compa Antioxidanmentioning
confidence: 91%
“…This abberant brain and neurotransmission condition leads to Alzheimer's disease (AD) pathogenesis (Li et al, 2015;Willcox, Scapagnini, & Willcox, 2014) that contributes to increased global morbidity/mortality rate (US Burden of Disease Collaborators, 2013). The high catalytic efficiency (CE) of AChE and the importance of its inhibition in AD management has been an important research focus in the development of various therapeutic agents (Acharya, Dutta, Chaudhury, & De, 2018;Li et al, 2015;Olarewaju et al, 2018;Saravanaraman, Chinnadurai, & Boopathy, 2014;Taslimi & Gulçin, 2018;Yadav & Appukuttan, 2019;Yatesa et al, 2019;Zare-Zardini, Tolueinia, Hashemi, Ebrahimi, & Fesahat, 2013). Several synthetic AChE-inhibitory drugs have been developed for use against neurodegenerative diseases, such as dementia and AD; however, these drugs are associated with severe negative side effects (Ghribia, Ghouilaa, Omrib, Besbesb, & Janneta, 2014;Iannello et al, 2014;Kumar & Chowdhury, 2014).…”
Section: Introductionmentioning
confidence: 99%